Systemic therapies for medullary thyroid carcinoma: state of the art - Alejandro Román-González; Ines Califano; Marcio Concepción-Zavaleta; Fabian Pitoia; Sarimar Agosto Salgado (Therapeutic Advances in Endocrinology and Metabolism)
Medullary thyroid carcinoma (MTC) is a rare neuroendocrine tumor accounting for less than 5% of all thyroid cancers. An estimated 25% of cases are familial secondary to a germline mutation on the rearranged during transfection proto-oncogene ( RET ); this gene can be present as a somatic mutation in approximately 40%–60% of sporadic MTC tumors. There is an existing genotype-phenotype correlation in the clinical behavior of MTC, with the RET M918T variant associated with aggressive disease. The current systemic treatment profile for progressive metastatic MTC involves antiangiogenics multikinase inhibitors (MKI), specifically cabozantinib and vandetanib, and high-specific RET inhibitor therapy. Decisions on the timing of systemic therapy initiation in this population should involve multidisciplinary care and individualization on a case-by-case scenario; a comprehensive evaluation of performance status, tumor burden, progression rate, medical comorbidities, possible medication interactions, and goals of care must be considered in a patient-centered approach. This review summarizes the evidence on the safety, efficacy, and limitations of systemic therapies for MTC; the aim is to empower clinicians with the knowledge to optimally manage patients with advanced, progressive, or metastatic MTC.